1997
DOI: 10.5144/0256-4947.1997.175
|View full text |Cite
|
Sign up to set email alerts
|

Photochemotherapy for Vitiligo: Seven Years' Experience at a University Hospital

Abstract: Photochemotherapy has been the most successful treatment of vitiligo to date. In this study we tried to evaluate the efficacy, safety and patient acceptability of photochemotherapy (PUVA, or psoralen and ultraviolet A, therapy) for vitiligo patients treated in King Khalid University Hospital over the period of 1987-1994. The treatment success strongly depended on the number of treatments. More than 75% repigmentation was achieved in 42% of the patients who received 100 to more than 200 treatments. Unfortunatel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…This might be explained by the immunological effect of PUVA on circulating lymphocytes in active disease stages. A previous retrospective study, documented that disease stability did not influence the extent of re‐pigmentation (17). Acral lesions showed a worse response to either oral PUVA or NB‐UVB therapy than lesions in other sites, as previously documented (18–20).…”
Section: Discussionmentioning
confidence: 56%
“…This might be explained by the immunological effect of PUVA on circulating lymphocytes in active disease stages. A previous retrospective study, documented that disease stability did not influence the extent of re‐pigmentation (17). Acral lesions showed a worse response to either oral PUVA or NB‐UVB therapy than lesions in other sites, as previously documented (18–20).…”
Section: Discussionmentioning
confidence: 56%
“…When the patients were interviewed, regarding the history of previous treatment about 57% of the patients had taken past medications for vitiligo. At the same time, in a study conducted by Al-Khawajah reported out of 52 patients, 23 patients sought treatment by folk (herbal) medicine[15]. The major treatments given in this study were topical tacrolimus (53%), PUVASol (43%) and NBUVB (22%).…”
Section: Resultsmentioning
confidence: 92%
“…SOD is an anti-inflammatory enzyme induced by exposure to various forms of oxidative stress, and high levels are expected in vitiliginous skin because of the imbalance in the oxidant/antioxidant system [10]. PUVA also has an inhibitory effect on circulating lymphocytes [30]. Antioxidants attenuate the damaging effects of ROS and can impair and/or reverse many of the events that contribute to epidermal toxicity and disease; however, increased or prolonged free radical action can overwhelm ROS defense mechanisms [28].…”
Section: Discussionmentioning
confidence: 99%